FAKTOR-FAKTOR YANG MEMPENGARUHI PEMANFAATAN CATATAN ATAS LAPORAN KEUANGAN (CALK) OLEH PENGGUNA LAPORAN KEUANGAN DAERAH DI OPD KOTA PALEMBANG - Ningsih, Nurul Hutami; Welly, Welly (Balance : Jurnal Akuntansi dan Bisnis, 2017)
ABSTRACT This research aims to examine the use of  Notes to The Financial Statements to the leaders, supervisory, or agencies in regional work organization (OPD) for having a good decision function of government to obtain the valid result, so this research using three variables independent such as, education, experience, and organizational culture. The population in this research was a government agency in Palembang. Samples were selected by using purposive sampling which the criteria was the leaders, supervisory, or agencies. The results showed that the variables of education, experience, socio culture affect significantly positive on the using of Notes to The Financial Statements.